2020
DOI: 10.2147/dddt.s278918
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality by Design (QbD)-Based Numerical and Graphical Optimization Technique for the Development of Osmotic Pump Controlled-Release Metoclopramide HCl Tablets</p>

Abstract: Purpose: To develop the osmotically controlled-release gastroprokinetic metoclopramide HCl tablets, using quality by design (QbD)-numerical and graphical optimization technique for the treatment of gastroparesis and prophylaxis of delayed nausea and vomiting induced by low-high emetogenic chemotherapy. Methods: Formulations were designed by central composite design using Design Expert version 11.0.0, with osmogen concentration (X 1), orifice size (X 2), and tablet weight gain after coating (X 3) as input and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…On the contrary, formulations (F9-F16) containing a high level (+1) of Methocel ™ K4M released tramadol HCl at a zero-order rate, but the erratic release behavior was observed (see Table 6 and Figure 2B), which may be possibly associated with the excessive swelling of some units within 6-12 h. Lin et al also reported that when the outer coating is non-extensible and could not uphold a high intrinsic osmotic pressure, the osmotic pump suffered a failure which may lead to burst release (Lin et al, 2002). Only two formulations, F3 and F4, followed zero-order release rates, Y4 (0.992 and 0.994) which was observed independent of orifice size (F3 = 0.2 mm, F4 = 0.8 mm), however, Farooqi et al reported that initial burst release from osmotic tablets was due to large orifice size and minimal weight gain after coating (Farooqi et al, 2020). Moreover, in the present work, the maximum release was found to be more than 90%, up to 16 h. This shows that the inclusion of matrix forming polymer effectively controlled the tramadol HCl release rate, especially in the initial hours; however, at the 12th hour, the effect started to decrease (see Figures 3A-D, 4A-D).…”
Section: In-vitro Drug Release Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, formulations (F9-F16) containing a high level (+1) of Methocel ™ K4M released tramadol HCl at a zero-order rate, but the erratic release behavior was observed (see Table 6 and Figure 2B), which may be possibly associated with the excessive swelling of some units within 6-12 h. Lin et al also reported that when the outer coating is non-extensible and could not uphold a high intrinsic osmotic pressure, the osmotic pump suffered a failure which may lead to burst release (Lin et al, 2002). Only two formulations, F3 and F4, followed zero-order release rates, Y4 (0.992 and 0.994) which was observed independent of orifice size (F3 = 0.2 mm, F4 = 0.8 mm), however, Farooqi et al reported that initial burst release from osmotic tablets was due to large orifice size and minimal weight gain after coating (Farooqi et al, 2020). Moreover, in the present work, the maximum release was found to be more than 90%, up to 16 h. This shows that the inclusion of matrix forming polymer effectively controlled the tramadol HCl release rate, especially in the initial hours; however, at the 12th hour, the effect started to decrease (see Figures 3A-D, 4A-D).…”
Section: In-vitro Drug Release Studiesmentioning
confidence: 99%
“…The independent variables were NaCl (X1) as an osmotic agent, Methocel ™ K4M (X2) as a release rate controlling agent, percent weight gain after coating with Opadry ® CA (X3), and orifice diameter (X4), which were set at low and high levels coded as +1 and −1 respectively. The selection of in put variables and their level ranges were based on preliminary reported studies (El-Zahaby et al, 2018;Farooqi et al, 2020), so that their influence on critical response variables, drug release (%) at 2 h (Y1), 12 h (Y2), 16 h (Y3), and RSQ zero (Y4) can be studied (Shah and Prajapati, 2019). A stepwise regression analysis was conducted using a full factorial design to determine the influence of significantly controlling input factors on response variables (Xue et al, 2015).…”
Section: Design Of Experiments (Doe) For Elementary Osmotic Tabletsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MTC was previously prepared in a floating matrix tablet ( Singh et al 2007 ). Retention of MTC in the stomach guarantees the prolonged effect and improves systemic availability, which is considered to overcome nausea or vomiting due to chemotherapy treatment or migraine disease ( Friedman et al, 2008 , Sharif et al, 2019 , Farooqi et al, 2020 ). Also, the MTC’s prolonged effect formulations overcome the rapid systemic or plasma concentration dropping due to MTC’s short half-life of 5 to 6 h ( Zabirowicz,Gan 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by using the technique of controlled release and bioavailability enhancement [3]. Controlled release pharmaceutical dosage forms are superior to conventional dosage forms of the same drugs due to reduced dosing frequency, improved pharmacological activity, and a reduction in the fluctuation of drug concentration in plasma resulting in efficient and prolonged therapeutic effect [4]. Extended-release drug delivery is beneficial to deliver the drug molecules with a short plasma half-life.…”
Section: Introductionmentioning
confidence: 99%